Pengaruh Green Practices, Functional Value, Satisfaction, dan Word of Mouth terhadap Revisit Intention pada Hotel Mercure Grand Mirama - Priskadina Febriati; Erna Andajani; Veny Megawati (Widya Manajemen, 2022)
The result of this research has a goal to understand there effect of Green Practices, Functional Value, Satisfaction, and Word of Mouth on Revisit Intention to Hotel Mercure Grand Mirama Surabaya. This research used 150 people's data and the collected data were analyzed using Smart PLS software version 3.2.2. The results of this study show that Green Practices have a positive and significant effect on Functional Value, Satisfaction, Word of Mouth, and Revisit Intention. Then Functional Value has a positive and significant effect on Satisfaction, Word of Mouth, and Revisit Intention. And Satisfaction has no significant effect on Word of Mouth but has a positive and significant effect on Revisit Intention.